Meso-Macro Modelling of Coated Forming Tools under Thermal Shock Conditions - Sauerland, Kim-Henning; Mahnken, Rolf (PAMM)

An error indicator for parameter identification with stabilized mixed tetrahedrals - Widany, Kai-Uwe; Mahnken, Rolf (PAMM)

Stabilized mixed triangular finite elements at large deformations using area bubble functions - Caylak, Ismail; Mahnken, Rolf; Widany, Kai-Uwe (PAMM)

Reibungsdämpfung in ausgedehnten, verschraubten Fügestellen - Hölzl, Johannes Sebastian; Sextro, Walter (PAMM)
Bei der Konstruktion von Maschinen ist es oftmals erforderlich, Schwingungen minimal zu halten. Um z.B. die Lebensdauer zu erhöhen, Material einzusparen oder den Geräuschpegel gering zu halten muss oft ein großer Aufwand zur Dämpfung von auftretenden Schwingungen betrieben werden. In vielen technischen Anwendungen werden Einzelteile miteinander verschraubt. Diese Fügestellen können gezielt und mit wenig Aufwand zur Schwingungsdämpfung herangezogen werden. Die Berechnung des dynamischen Verhaltens verschraubter Strukturen stellt immer noch eine Herausforderung dar. Es wurde eine Methode entwickelt, um den eingeschwungenen Zustand elastischer, miteinander verschraubter Körper mit rauen Fügestellen bei periodischer Anregung zu berechnen. Als Basis dienen Finite Elemente Modelle der einzelnen Teile, deren Freiheitsgrade durch modale Kondensation reduziert werden. Unter Anwendung des Verfahrens von Ritz und Galerkin wird eine Näherungslösung für den eingeschwungenen Zustand des nichtlinearen, gekoppelten Systems ermittelt. Abhängig von den Schraubenvorspannkräften sowie den bestimmenden Parametern der Kontaktflächen, Rautiefe und Reibungskoeffizient, kann die Systemantwort berechnet und optimiert werden. Um die Berechnungsmethode zu verifizieren wurden Experimente durchgeführt. Der Vergleich zwischen Messung und Rechnung zeigt eine gute Übereinstimmung. ({©} 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim)

Solving optimal control problems by using inherent dynamical properties - Flaßkamp, Kathrin; Ober-Blöbaum, Sina; Kobilarov, Marin (PAMM)

Simulation of a Hybrid-Forming Process using Temperature- and Rate-Dependent Viscoplastic Material Models - Sauerland, Kim-Henning; Schneidt, Andreas; Mahnken, Rolf (PAMM)

Stabilized Mixed Tetrahedrals with Volume and Area Bubble Functions at Large Deformations - Widany, Kai-Uwe; Caylak, Ismail; Mahnken, Rolf (PAMM)

FEM Simulation of a Micromechanical Model for Textured Polycrystalline Shape Memory Alloys with n-Variants - Wilmanns, Stefan; Mahnken, Rolf (PAMM)

Modeling of bainitic phase transformation - Schneidt, Andreas; Mahnken, Rolf (PAMM)

Deformation and Damage Analysis of a Hybrid-Forming Tool under Thermal Shock Conditions - Mahnken, Rolf; Sauerland, K.-H.; Schneidt, A.; Gockel, F.-B. (PAMM)

Modellierung der Umwandlungsplastizität und Viskoplastizität niedrig legierter Stähle - Schneidt, Andreas; Mahnken, Rolf (PAMM)

Asymmetric effects of polymers in finite thermoviscoplasticity - Shaban, Ahmed; Mahnken, Rolf (PAMM)

Simulation of brittle crack growth in functionally graded materials - Mahnken, Rolf (PAMM)

On the stabilization of tetrahedral finite elements using volume and area bubble functions - Caylak, Ismail; Mahnken, Rolf (PAMM)

Experimentelle Untersuchungen zum Thermoschock beim Hybridumformprozess - Schneidt, Andreas; Mahnken, Rolf (PAMM)

Simulation of asymmetric effects for shape memory alloys - Wilmanns, Stefan; Mahnken, Rolf (PAMM)

Material Simulation and Damage Analysis at Thermal Shock Conditions - Gockel, Franz-Barthold; Mahnken, Rolf (PAMM)

Simulation of Rate Dependent Plasticity of Polymers - Shaban, Ahmed; Mahnken, Rolf (PAMM)

Simulation of Asymmetric Effects in Plasticity - Mahnken, Rolf (PAMM)

Analysis of the Forced Vibration of Two Bolted Half-Pipes with Extended Friction Contacts - Genzo, Alexander; Sextro, Walter; Popp, Karl (PAMM)
The present paper deals with the forced vibration analysis of a test structure. The test structure consists of two parts, an upper and a lower half pipe, joint in two bolted flanges which represent the extended friction contacts. Depending on the clamping loads different normal pressure distributions can be established in the contact interfaces. Since the test structure is loaded with a harmonic external force relative displacements occur in the contact interface. This leads to microslip effects affecting the dynamic behaviour. The experimental validation of the calculation method accounting for these effects is shown by comparing measured and calculated frequency response functions (FRF). (Â{©} 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Analysis of the Forced Vibration of Two Bolted Half-Pipes with Extended Friction Contacts - Genzo, Alexander; Sextro, Walter; Popp, Karl (PAMM)
The present paper deals with the forced vibration analysis of a test structure. The test structure consists of two parts, an upper and a lower half pipe, joint in two bolted flanges which represent the extended friction contacts. Depending on the clamping loads different normal pressure distributions can be established in the contact interfaces. Since the test structure is loaded with a harmonic external force relative displacements occur in the contact interface. This leads to microslip effects affecting the dynamic behaviour. The experimental validation of the calculation method accounting for these effects is shown by comparing measured and calculated frequency response functions (FRF). (Â{©} 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Unkontrollierbare Bewegungen ebener Mechanismen mit Gelenkspiel - Hofmeister, Adolf; Sextro, Walter; Röschel, Otto (PAMM)
In dieser Arbeit wird ein analytisches Berechnungsverfahren vorgestellt, mit dem der gesamte Positions- und Orientierungsraum (ErrorWorkspace) ebener Mechanismen mit spielbehafteten Gelenken kinematisch beschrieben bzw. dargestellt werden kann. Für die Berechnung wird der gesamte Positions- und Orientierungsraum im Kinematischen Bildraum dargestellt, wobei auf besondere Merkmale eingegangen wird. Der ErrorWorkspace, der mit Hilfe des Berechnungsverfahren bestimmt wird, wird an einem Koppelgetriebe, an einem Filmgreifergetriebe und an einem Double-rocker four-bar mechanism mit Kurbelantrieb dargestellt und analysiert. ({©} 2005 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Experimental and Numerical Investigations for Cyclic Thermal Shocks - Gockel, Franz-Barthold; Mahnken, Rolf (PAMM)

Hysteretic Friction of a Sliding Rubber Element - Lindner, Markus; Sextro, Walter; Popp, Karl (PAMM)
Friction, especially friction of elastomers, can cause acoustic problems like noise, squeal and comfort drawbacks like vibrations and wear. Therefore, rubber friction affects the function of many products in technical applications, e.g. seals, belts and tires. It can be classified according to different physical phenomena like adhesion, hysteresis, cohesion and viscous friction, see [3]. The topic of this paper is hysteresis friction of rubber that is caused by the energy dissipation due to internal material damping during the process of deformation. The deformation itself occurs during the sliding of a rubber element across the micro-scaled asperities of a rough surface. In this paper, the sliding process of a rubber element over real surfaces is simulated in time domain and compared to experiments. (Â{©} 2004 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)

Stress mode dependent weighting functions for simulation of asymmetric creep effects - Mahnken, Rolf (PAMM)

Erzwungene Schwingungen von elastischen Mehrkörpersystemen mit Reibkontakten - Genzo, Alexander; Sextro, Walter; Popp, Karl (PAMM)
Im Folgenden wird eine Berechnungsmethode vorgestellt, die es erlaubt, das räumliche Schwingungsverhalten eines elastischen Mehrkörpersystems (EMKS) mit Reibkontakten in rechenzeit- und speicherplatzsparender Form zu analysieren. Der von trockener Reibung und Mikroschlupf geprägte, nichtlineare Dämpfungsmechanismus in den Reibkontakten eines EMKS wird dabei realitätsnahe abgebildet. Die Plausibilität der mit der Methode gewonnenen Berechnungsergebnisse wird beispielhaft an einem einfachen EMKS, einem in Längsrichtung geteilten, einseitig eingespannten Balken gezeigt. Für den geteilten Balken werden die Frequenzgänge des Torsionswinkels um die Längsachse und der Auslenkung um die biegeweiche Achse berechnet.

Design of Friction Dampers for Mistuned Bladed Disks - Panning, Lars; Sextro, Walter; Popp, Karl (PAMM)
Friction damping devices such as underplatform dampers are widely used in turbomachinery applications to reduce blade vibration amplitudes. In this paper, a model is presented briefly to calculate the forced response of mistuned bladed systems with friction dampers. Some results will give an insight in the vibrational behavior of frictionally damped bladed disks and how the damping gain is affected by the damper properties.

Anisotropic creep modeling based on elastic projection operators - Mahnken, Rolf (PAMM)